Terapi Relaksasi Guide Imagery untuk mengurangi Nyeri pada Pasien Gastritis - Sari, Putri Irwanti; Nafasha, Reza; Oktaria, Rina; Nurhusna, Nurhusna (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2024)
This study aims to evaluate the effectiveness of guided imagery relaxation therapy in reducing pain in patients with gastritis. Gastritis, characterized by inflammation of the stomach lining, often leads to significant epigastric pain, affecting patients' quality of life. The research method employed is a literature review, which collects and analyzes data from various previous studies regarding the application of guided imagery as a non-pharmacological intervention. The results indicate that guided imagery therapy can significantly reduce pain levels in gastritis patients. Before the intervention, the majority of patients experienced moderate to severe pain; however, after the therapy was applied, many patients reported a reduction in pain to the point of experiencing none at all. Thus, this therapy has proven to be safe and effective, with no adverse side effects. This study recommends the implementation of guided imagery therapy as an alternative in pain management for gastritis patients and encourages further research to explore the long-term benefits of this intervention.